Opening Space for Non-Research Articles: Supporting Diversity and Balance in Scientific Health Publications - Abdullah Al Mamun; Rafif Naufi Waskitha Hapsari; Heru Santoso Wahito Nugroho (Health Dynamics, 2024)
Not mandatory